The Effect of Thickness and Mesh Spacing on the Impact Resistance of Ferrocement Slab - Muda Z.C.; Alam M.A.; Syamsir A.; Sulleman S.; Beddu S.; Mustapha K.N.; Thiruchelvam S.; Ismail F.B.; Usman F.; Kamal N.L.M.; Birima A.H.; Itam Z.; et al. (Institute of Physics Publishing, 2023)
Concrete slabs; Cracks; Drops; Reinforced concrete; Reinforcement; Drop weight impact; Linear correlation; Low impacts; Mesh reinforcement; Mesh spacing; Projectile tests; Slab thickness; Steel balls; Mesh generation; cement; concrete; concrete structure; crack; impact; reinforcement; research work; spacing; weight